Microsatellite markers for the biogeographically enigmatic sandmyrtle (Kalmia buxifolia, Phyllodoceae: Ericaceae). (5th June 2019) - Gillespie, Emily L.; Madsen‐McQueen, Tesa; Eriksson, Torsten; Bailey, Adam; Murrell, Zack E.
Abstract : Premise: Microsatellite markers were developed for sandmyrtle, Kalmia buxifolia (Ericaceae), to facilitate phylogeographic studies in this taxon and possibly many of its close relatives. Methods and Results: Forty‐eight primer pairs designed from paired‐end Illumina MiSeq data were screened for robust amplification. Sixteen pairs were amplified again, but with fluorescently labeled primers to facilitate genotyping. Resulting chromatograms were evaluated for variability using three populations from Tennessee, North Carolina, and New Jersey, USA. Eleven primer pairs were reliable and polymorphic (mean 3.92 alleles), one was reliable but monomorphic, and four were not reliable. The markers exhibited lower heterozygosity (mean 0.246) than expected (mean 0.464). Cross‐amplification in the remaining nine Kalmia species exhibited a phylogenetic pattern, suggesting broad applicability of the markers across the genus. Conclusions: These microsatellite markers will be useful in population genetics and species boundaries studies of K. buxifolia, K. procumbens, and likely all other Kalmia species.